Qualitative comparative analysis (QCA): An application for the industry (2011)
This article examines the management in Colombian industrial sectors using qualitative comparative analysis (QCA). This method conceptualizes cases as combinations of attributes and use Boolean algebra to derive simplified expressions of combinations that lead to a specific outcome. In this analysis, we show the value of this method for studying the management in the industrial from different approaches.